Knowledge of dental students of avulsed permanent teeth - Habekost, Ana Paula Zambarda; Miotto, Daniela Elisa; Gomes, Fernando Vacilotto; Moraes, João Feliz Duarte de; Oliveira, Marília Gerhardt de; Weber, João Batista Blessmann; Marzola, Clovis (Revista de Ciências Médicas e Biológicas, 2010)
<!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <mce:style><! st1\:*behavior:url(#ieooui) –> <!–[endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –> <!–[endif]–>The survival of an avulsed permanent tooth depends on the management and the appropriate treatment of the injury by the dental surgeon. The aim of this study was to assess the knowledge of first-year and last-year dental undergraduates on guidelines for management and treatment of tooth avulsion. A 10-item multiple-choice questionnaire was distributed among 65 first-year and 60 last-year dental undergraduates at the School of Dentistry, Pontifícia Universidade Católica do Rio Grande do Sul (PUCRS), Brazil, between 2006 and 2007. Answers were graded 0 to 3. The results revealed a low level of knowledge among first-year and last-year students on the management and treatment of permanent avulsed teeth. Knowledge of last-year undergraduates of tooth avulsion was lower than what is required for a future dental surgeon. In conclusion, there is a need to improve the knowledge of dental students in the guidelines for the management of tooth avulsion. Because tooth avulsion is the most prevalent lesion in dentoalveolar traumas, it is of the utmost importance that dental surgeons be prepared to treat it properly, avoiding damage to neighboring teeth and structures, and esthetic, functional, psychosocial and therapeutic implications for the patient.